The Journey of A Math: As a Mathematics Learning Innovation - Husnah, Annisa Ul; Hidayat, Muhammad Alif; Jannah, Miftahul (Universitas Pendidikan Indonesia (UPI), 2021)
In the era of the Industrial Revolution 4.0, science and technology played an important role in the future. Therefore, education is fundamental in the formation and development of human resources. Thus, they can contribute to the development of science and technology, especially in Mathematics. Mathematics has an important role in the future, but as is well-known Mathematics is one of the subjects that is considered difficult. Many students complain about this lesson for several reasons, such as the monotonous learning and the way the teacher does not vary. Thus, it is difficult to understand. To solve this problem, there is an innovation called TJAM. TJAM is an application that is devoted to learning Mathematics. The features of TJAM are as follows: MyMaths, Math Stories, FunMath, and MathUrgent features. The research method we use is qualitative. The purpose of TJAM is to make students like mathematics and not be afraid of mathematics because in TJAM students can find features that will help them in learning Mathematics. TJAM has an advantage when compared to similar applications, TJAM has the FunMath and MathStorie features where these two features will make it easy for students to learn mathematics. Through TJAM, students are expected to like math and be helped by the features provided.